Adult education from a psychological perspective - Oliwia McFarlane; Milena Wojciechowska; Katarzyna Dudzik; Oliwia Łakomska (Kazimierz Wielki University, 2019)
In the modern world, civilizational progress has become an important justification for the need of lifelong learning. Transformations of technical, technological, scientific, cultur-al and social nature require constant adjustment, in which the education process plays a tremendous role. One cannot underestimate the fact that the current ability to adjust to ubiquitous transformations, innovations and requirements of the job market will also impact the socioeconomic situation of the future societies. The effectivity of adult learning is influenced by the variety of factors, amongst which psychological variables, including motivation, play a crucial role. This article presents the specificity of adult education, and its practical implications.